Chemical characterization of covered and hulness barley cultivars - Mayer, Elveni Teresinha; Fuke, Gitane; Nörnberg, José Laerte; Minella, Euclydes (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to determine the chemical composition of different covered and hulness barley cultivars grains and to classify them according to distinctive nutritional groups. Seventeen cultivars from 2005 crop of Embrapa Trigo, Passo Fundo, RS, Brazil, were utilized. The chemical determinations were based on Official Methods of Analysis of the AOAC International. Significative differences between integral cultivars in relation to crude protein, ash, ether extract, total fiber and non-fibrous carbohydrate were observed, however, there were no differences for fiber content and soluble fiber. In the hulness grain, differences were observed. The non-fibrous carbohydrate was an exception and, in this case, the hull’s process promoted the fraction’s reduction, specially in the total fiber and insoluble fiber content. Variation in the bromatological composition occurs because of the genetic variability of cultivars and due to the hulness.